Perioperative Point-of-Care Ultrasound in Children - Karen Boretsky (MDPI AG, 2020)
Anesthesiologists and other acute care physicians perform and interpret portable ultrasonography-point-of-care ultrasound (POCUS)-at a child's bedside, in the perioperative period. In addition to the established procedural use for central line and nerve block placement, POCUS is being used to guide critical clinical decisions in real-time. Diagnostic point-of-care applications most relevant to the pediatric anesthesiologist include lung ultrasound for assessment of endotracheal tube size and position, pneumothorax, pleural effusion, pneumonia, and atelectasis; cardiac ultrasound for global cardiac function and hydration status, and gastric ultrasound for aspiration risk stratification. This article reviews and discusses select literature regarding the use of various applications of point-of-care ultrasonography in the perioperative period.